Social Networks and ICTs, their role in 21st century higher education - Martínez Solana, María Yolanda (Historia y Comunicación Social, 2014)
21st century has brought a transformation of the cultural context of societies, as a result of the appearance of different sources of knowledge and means of information transmission, which have affected all academic environments. Instructors are forced to be trained in use, concepts and range of social networks and ICTs, even though these may not substitute the pre-existent educational tools. This leads to a redefinition of the educational system, in order to embrace a genuine educational technology. The birth of the Digital Agora has knocked down the limits to content access while, at the same time, compartmentalizing knowledge, and the inadequate use of new technologies might entail non-desirable consequences.
Keywords: Social Networks; ICT; Higher Education; Digital Agora; Instructors; Knowledge.